P108 How do men who have sex with men fare in integrated sexual health centres? an audit of hepatitis b vaccination rates before and after integration. (18th May 2015) - Wielding, Sally; Ma, Andy; Clutterbuck, Dan
Abstract : Introduction: In Scotland, Health Improvement Scotland (HIS) standards require that 70% of men who have sex with men (MSM) attending specialist sexual health services who are not known to already be immune should receive at least one dose of hepatitis B vaccine. The integration of sexual health services could theoretically disadvantage MSM. Objectives: Audit was performed before and after integration of genitourinary medicine (GUM) and sexual and reproductive health (SRH) services in April 2011 to assess the impact of service redesign. Methods: HBV vaccination eligibility, uptake and course completion by MSM registering as new patients in general sexual health and specialist MSM clinics was audited retrospectively for 6 month periods before and after integration of services. Results: Pre-integration 239 MSM registered for a first episode of care: 62.8% were eligible for vaccination. Post-integration 25.3% of 343 new patients were eligible. The proportion of eligible men receiving at least 1 dose of vaccination pre- and post-integration was unchanged (130/150 = 86.7% vs 78/87 = 89.7%, p = 0.6458, Chi 2 0.2223043) However, there was a significant reduction in the proportion of men receiving 3 doses of vaccination; (76/150 = 50.7% vs 30/87 = 34.5%, p = 0.0157, Chi 2 5.834). Discussion: SRH services continued to provide very high levels of initiation of HBV vaccination, even during the period immediately after integration when clinic accommodation, pathways and staffing were in a state of change. The reduced completion rates of a 3-dose course post-integration suggest that clinic access, availability and acceptability for MSM as well as recall arrangements should be explored.